A postmortem study on the volume of the human kidney - Johora, Fatema; Nurunnabi, Abu Sadat Mohammad; Siddiqua, Dilruba; Hena, Hasna; Ara, Shamim (Journal of Dhaka Medical College, 2015)
Context: Kidney volume is a sensitive index of kidney size for the detection of renal abnormalities. It is also excellent predictor of renal function and correlates very well with body indexes. The present study was done on cadaveric specimens to see the age related changes in the volume of the kidney in a Bangladeshi population and to compare with the previous local and foreign studies. Methods: This cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, based on collection of 140 post mortem human kidneys from 70 unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. All the samples were divided into three age groups including A (10-19 years), B (20-39 years) and C (40-59 years). The length, breadth and thickness of each kidney were measured by using a slide calipers and recorded. Then the volume was determined by using prolate ellipsoid formula i.e. length × breadth × thickness × 0.52. Results: The volume of the right and left kidneys were found 54.46±4.02 cm3 and 53.15±1.98 cm3 in group A, 78.31±10.41 cm3 and 75.90±8.32 cm3 in group B, 74.47±6.22 cm3 and 73.34±6.80 cm3 in group C. No statistically significant difference was found between the right and the left kidney in any group. However, statistically significant differences were evident between A & B and A & C (P<0.001). Conclusion: No difference was found in volume between the right and the left kidney in any group. However, kidney volume was found to increase with advancing age in apparently healthy Bangladeshi people. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22698 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 73-77